Engineering the coordination environment in atomic Fe/Ni dual-sites for efficient oxygen electrocatalysis in Zn-air and Mg-air batteries - Zhang, Xiaomeng; Li, Yuan; Jiang, Min; Wei, Jianxu; Ding, Xinxin; Zhu, Changyan; He, Hao; Lai, Hongchang; Shi, Junyu (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
[Display omitted] •Atomically dispersed Fe, Ni Dual Active Centers on defect-rich porous nitrogen and sulfur carbon frameworks were achieved.•AC-STEM and XAS analysis and fitting proved the neighboring Fe-N5-S and Co-N5-S dual active structure.•Fe, Ni-SAs/DNSC showed excellent ORR in both alkaline and neutral medium.•The as-prepared Fe, Ni-SAs/DNSC catalyst revealed remarkable performance in flexible solid-state metal-air batteries. Rational design the single atomic catalyst with excellent activity, stability and high exposure of active sites is a significant challenge. Here, we report an atomically dispersed iron and nickel co-anchored on defect-rich porous nitrogen and sulfur carbon frameworks (denoted as Fe, Ni-SAs/DNSC) with tailored coordination environment, The Fe, Ni-SAs/DNSC electrocatalyst displays outstanding catalytic activity for oxygen reduction reaction (ORR) with an onset potential (Eonset) of 1.03 V (vs. RHE), half-wave potential (E1/2) of 0.88 V (vs. RHE) as well as superior stability. The catalyst also shows a superior oxygen evolution reaction (OER) activity. When Fe, Ni-SAs/DNSC catalyst is employed as an air cathode, the Zn-air battery displays superior performance with a large peak power density of 160 mW cm−2, high energy density of 962.8 Wh kgZn-1 and cycling stability. Also, the Fe, Ni-SAs/DNSC-based liquid and flexible solid-state Mg-air batteries deliver a large peak power density of 76 mW cm−2, high energy density of 1653 Wh kgMg–1 and superior durability (Over 78 h at 20 mA cm−1). Furthermore, DFT calculations reveal that the doped S atom and carbon vacancy can weaken the binding strength between oxygen intermediates and Fe active site and improve the desorption of *OH step during the ORR process. This work provides insights into the design dual single atomic catalyst with a tailored coordination environment.